Botnet detecting method based on group-signature filter - WANG Jin-song1; LIU Fan1; ZHANG Jian3 (Tongxin xuebao)
A botnet detecting method was presented based on group-signature filter,suitable for the traditional signatures matching algorithm.Using multiple member signatures to filter the packets of hosts from Intranet,the proposed method is able to handle the shortened and scattered signatures at a space expense of O（tmn）.The simulated experiment proves the correctness and validity of the detecting method.